A NiCo LDH nanosheet array on graphite felt: an efficient 3D electrocatalyst for the oxygen evolution reaction in alkaline media. Issue 12 (21st May 2021) - Ye, Chen; Zhang, Longcheng; Yue, Luchao; Deng, Biao; Cao, Yang; Liu, Qian; Luo, Yonglan; Lu, Siyu; Zheng, Baozhan; Sun, Xuping
Abstract : A NiCo LDH nanosheet array on graphite felt is an efficient 3D OER catalyst with the need for an overpotential of 249 mV to drive 20 mA cm −2 in 1.0 M KOH. Abstract : The development of efficient electrocatalysts from Earth-abundant elements for the oxygen evolution reaction (OER) is highly desired. Here, we report the electrodeposition of a NiCo layered double hydroxide nanosheet array on graphite felt (NiCo LDHs/GF) as a 3D OER electrocatalyst. Such NiCo LDHs/GF exhibits superior electrocatalytic activity with the need for an overpotential of 249 mV to drive a current density of 20 mA cm −2 in 1.0 M KOH. It also shows strong long-term electrochemical durability with its activity being maintained for at least 24 h.